Treatment of Ovarian Clear Cell Carcinoma: A Case of Successful Management With Targeted Therapies - Sydney Pence; Kellie Rath; Aine Clements (Case Reports in Obstetrics and Gynecology)
Conclusion: The use of targeted therapies as well as the combination of nivolumab and ipilimumab is a promising option in advanced and recurrent cases of ovarian clear cell carcinoma.